2021
DOI: 10.1002/ajim.23224
|View full text |Cite
|
Sign up to set email alerts
|

Working near a supervised injection facility: A qualitative study of perspectives of firefighter‐emergency medical responders

Abstract: Background While firefighter‐emergency medical responders (FF‐EMR) are important stakeholders in cities considering the implementation of a supervised injection facility (SIF), there is little information on perspectives of first responders who serve these communities. The aim of the present study was to identify FF‐EMR perspectives on working near a SIF. Methods FF‐EMRs from Vancouver Fire and Rescue Services completed an online survey that queried participant perspectives on working near a SIF. Results Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…There is a potential for recall bias as respondents were stationed at Firehall 2 up to 12 years ago. However, participant anonymity and consistency in response themes in our previous report (Pennington et al, 2021) increases our confidence that these findings accurately capture first-responder attitudes toward working near the SIF in Vancouver. In addition, our sample lacked demographic diversity.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…There is a potential for recall bias as respondents were stationed at Firehall 2 up to 12 years ago. However, participant anonymity and consistency in response themes in our previous report (Pennington et al, 2021) increases our confidence that these findings accurately capture first-responder attitudes toward working near the SIF in Vancouver. In addition, our sample lacked demographic diversity.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, peer support and self-care may be important components to be considered for programming. Furthermore, in our previous qualitative report on firefighter/paramedic perspectives of working near an SIF, first responders emphasized the importance of limiting the duration of their assignment at Firehall 2 to mitigate negative effects on physical and mental health (Pennington et al, 2021). Finally, in a previous study emergency service personnel reported safety concerns when considering SIF implementation due to previous experience with calls involving substance use (Perlmutter et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations